A Comprehensive Assessment of Family Physician Gender and Quality of Care: A Cross-Sectional Analysis in Ontario, Canada. Issue 3 (March 2016) - Dahrouge, Simone; Seale, Emily; Hogg, William; Russell, Grant; Younger, Jaime; Muggah, Elizabeth; Ponka, David; Mercer, Jay
Abstract : Background: Studies evaluating primary care quality across physician gender are limited to primary and secondary prevention. Objectives: Investigate the relationship between family physician gender and quality of primary care using indicators that cover 5 key dimensions of primary care. Research Design: Cross-sectional analysis using linked health administrative datasets (April 1, 2008 to March 31, 2010). Subjects: All family physicians working in the 3 main primary care models in the province of Ontario (Canada), providing general care and having a panel size >1200. Measures: Indicators of cancer screening (3), chronic disease management (9), continuity (2), comprehensiveness (2), and access (5). Results: A total of 4195 physicians (31% female) were eligible. Adjusting for provider and patient factors, patients of female physicians were more likely to have received recommended cancer screening (odds ratios [95% confidence interval (CI)] (OR) range: 1.24 [1.18–1.30], 1.85 [1.78–1.92]) and diabetes management (OR: 1.04 [1.01–1.08], 1.28 [1.05–1.57]). They had fewer emergency room visits (rate ratio [95% CI] (RR) range: 0.83 [0.79–0.87]) and hospitalizations (RR: 0.89 [0.86–0.93]), and higher referrals (RR: 1.12 [1.09–1.14]). There was evidence of effect modification by patient gender (female vs. male) for hospitalization (RR: 0.74 [0.70–0.79] vs. 0.96 [0.90–1.02]) and emergency room visits (RR: 0.84 [0.81–0.88] vs. 0.98 [0.94–1.01]). Lower emergency room visits were also more evident in more complex patients of female physicians. There were no significant differences in the continuity or comprehensiveness measures. Conclusions: The indicators assessed in this study point to a benefit for patients under the care of female physicians. Potential explanations are discussed.